The impact of market orientation on the internationalisation of SMEs - Fernandes, Cristina (2020)
Purpose – A key point in the internationalisation process of companies comes with the choice of international market. Following this choice, the results companies may thereby obtain help in measuring their level of international performance. This study aims to measure the impact of internationalisation processes in keeping with company market orientations (MOs) through measuring their effect on international performance. Design/methodology/approach – The authors obtained the data from a questionnaire sent out by email to a total of 8,103 exporting companies and/or with interests in exporting (the study population) registered in the AICEP-Portugal Global database that provided the email addresses of the company representatives responsible for internationalisation. The authors received a total of 320 valid responses (sample). Findings – The results display a positive MO effect both on internationalisation processes and on international performance. The authors also note the importance of studying the influence of strategic orientations on internationalization processes, motivated by the particular SME’s characteristics. Originality/value – The authors aim to contribute to the study of the influence of the MO, both upstream and downstream, thus seeking to verify its impact on internationalization processes.